Chapter 1. Gene regulatory networks in neural crest development and evolution. - Nikitina, N; Sauka-Spengler, T; Bronner-Fraser, M (2009)
The neural crest is a multipotent migratory embryonic cell population that is present in all vertebrates, but missing from basal chordates. In this chapter, we discuss recent work in amphioxus, ascidians, lamprey, and gnathostomes that reflects the current state of knowledge of the evolutionary origin of this fascinating cell population. We summarize recent evidence for the ongoing diversification of the neural crest in several vertebrate species, with particular reference to studies in nontraditional vertebrate model organisms.